Editorial notes - Byambakhishig, Purevsuren (Studia Philosophiae Et Juris, 2024)
This is the 48th year this issue (39th) has been in your hands, and the journal "Studia Philosophiae Et Juris" published by the Institute of Philosophy of the Mongolian Academy of Sciences, has been published regularly since 1976. Since its inception, the academic journal "Studia Philosophiae Et Juris" has published the most important issues of its time in the fields of philosophy, sociology, political science, legal studies, religion, scientific research and political economy. Then, it must be noted that the analysis of the past and planning for the future by reflecting on the present are the nature of things in a three-hour sequence and a choice that is passed on to the next generation. Therefore, one can take a look back on the path we have considered, learn from it, and revitalize the research work that can become the basis of our main goal and the priority of our research work.